Assessment of cytotoxicity exerted by leaf extracts from plants of the genus Rhododendron towards epidermal keratinocytes and intestine epithelial cells. Issue 1 (December 2015) - Rezk, Ahmed; Al-Hashimi, Alaa; John, Warren; Schepker, Hartwig; Ullrich, Matthias; Brix, Klaudia
Abstract Background Rhododendron leaf extracts were previously found to exert antimicrobial activities against a range of Gram-positive bacteria. In this study, we investigated which of the extracts with these antimicrobial properties would be best suited for further exploitation. Specifically, the project aims to identify biologically active compounds that affect bacterial but not mammalian cells when applied in medical treatments such as lotions for ectopic application onto skin, or as orally administered drugs. Methods Different concentrations of DMSO-dissolved remnants of crude methanolRhododendron leaf extracts were incubated for 24 h with cultured epidermal keratinocytes (human HaCaT cell line) and epithelial cells of the intestinal mucosa (rat IEC6 cell line) and tested for their cytotoxic potential. In particular, the cytotoxic potencies of the compounds contained in antimicrobialRhododendron leaf extracts were assessed by quantifying their effects on (i) plasma membrane integrity, (ii) cell viability and proliferation rates, (iii) cellular metabolism, (iv) cytoskeletal architecture, and (v) determining initiation of cell death pathways by morphological and biochemical means. Results Extracts of almost allRhododendron species, when applied at 500 μg/mL, were potent in negatively affecting both keratinocytes and intestine epithelial cells, except material fromR. hippophaeoides var.hippophaeoides . Extracts ofR. minus andR. racemosum were non-toxic towards both mammalian cell types when used at 50 μg/mL, which was equivalent to their minimal inhibitory concentration against bacteria. At this concentration, leaf extracts from three other highly potent antimicrobialRhododendron species proved non-cytotoxic against one or the other mammalian cell type: Extracts ofR. ferrugineum were non-toxic towards IEC6 cells, and extracts ofR. rubiginosum as well asR. concinnum did not affect HaCaT cells. In general, keratinocytes proved more resistant than intestine epithelial cells against the treatment with compounds contained inRhododendron leaf extracts. Conclusions We conclude that leaf extracts from highly potent antimicrobialR. minus andR. racemosum are safe to use at 50 μg/mL in 24-h incubations with HaCaT keratinocytes and IEC6 intestine epithelial cells in monolayer cultures. Extracts fromR. rubiginosum as well asR. concinnum orR. ferrugineum are applicable to either keratinocytes or intestinal epithelial cells, respectively. Beyond the scope of the current study, further experiments are required to identify the specific compounds contained in those Rhododendron leaf extracts that exert antimicrobial activity while being non-cytotoxic when applied onto human skin or gastrointestinal tract mucosa. Thus, this study supports the notion that detailed phytochemical profiling and compound identification is needed for characterization of the leaf extracts from specificRhododendron species in order to exploit their components as supplementary agents in antimicrobial phyto-medical treatments.